Housing and Housing Policy in the Nordic Countries (Copenhagen : Nordic Council of Ministers, 2004)
Nordic countries are often thought to have broadly similar housing policies, because they have traditionally had similar policies in areas like education, health care and social services based on shared fundamental values. In housing, however, these countries have distinctive national differences in areas like housing finance, support policy, tenure legislation and rent policy.This book takes an in-depht look at housing and housing policies in the five Nordic countries: Denmark, Finland, Iceland, Norway and Sweden. The chapters describe, analyse and compare the following areas, in a thematic way:- Housing markets, housing production and housing standard- The roles of housing policy actors - national government, municipalities, private business, households and non-profit actors- Housing tenures and rent legislation - Housing consumption, housing expenditure and user costs - Housing support policy, housing finance and housing taxation - Physical planning and urban policy - Sustainable development of cities and housing areasThe differences between the housing policies of the Nordic countries mean that, taken together, these countries have experience of a wide range of approaches, policies and instruments. This combined experience can be used in assessing the value of particular policies and instruments in particular contexts and assessing how they can be made to work together as effectively as possible.